Interventions to improve work outcomes in work-related PTSD: a systematic review - Bonato Sarah; Cheng Chiachen; Cimo Adriana; Stergiopoulos Erene; Dewa Carolyn S (BMC, 2011)
Abstract Background Posttraumatic stress disorder acquired at work can be debilitating both for workers and their employers. The disorder can result in increased sick leave, reduced productivity, and even unemployment. Furthermore, workers are especially unlikely to return to their previous place of employment after a traumatic incident at work because of the traumatic memories and symptoms of avoidance that typically accompany the disorder. Therefore, intervening in work-related PTSD becomes especially important in order to get workers back to the workplace. Methods A systematic literature search was conducted using Medline, PsycINFO, Embase, and Web of Science. The articles were independently screened based on inclusion and exclusion criteria, followed by a quality assessment of all included articles. Results The systematic search identified seven articles for inclusion in the review. These consisted of six research articles and one systematic review. The review focused specifically on interventions using real exposure techniques for anxiety disorders in the workplace. In the research articles addressed in the current review, study populations included police officers, public transportation workers, and employees injured at work. The studies examined the effectiveness of EMDR, cognitive-behavioural techniques, and an integrative therapy approach called brief eclectic psychotherapy. Interestingly, 2 of the 6 research articles addressed add-on treatments for workplace PTSD, which were designed to treat workers with PTSD who failed to respond to traditional evidence-based psychotherapy. Conclusions Results of the current review suggest that work-related interventions show promise as effective strategies for promoting return to work in employees who acquired PTSD in the workplace. Further research is needed in this area to determine how different occupational groups with specific types of traumatic exposure might respond differently to work-tailored treatments.